A Critical Evaluation of the Biological Construct Skeletal Muscle Hypertrophy: Size Matters but So Does the Measurement - Haun, Cody T.; Vann, Christopher G.; Roberts, Brandon M.; Vigotsky, Andrew D.; Schoenfeld, Brad J.; Roberts, Michael D. (Frontiers in Physiology, 2019)
Skeletal muscle is highly plastic and has consistently been shown to morphologically respond to exercise training. Skeletal muscle growth in response to training has traditionally been referred to as skeletal muscle hypertrophy. This can manifest as increases in muscle mass, muscle thickness, muscle area, muscle volume, and/or muscle fiber cross sectional area (fCSA). Electron microscopy and biochemical techniques have also been used to investigate ultrastructural and protein-level alterations. Decades of research in this area of exercise physiology have promulgated a widespread hypothetical model of training-induced skeletal muscle hypertrophy in which fCSA increases are thought to be accompanied by proportional increases in myofibrillar protein. This has been posited to correspond to an increased number of sarcomeres in parallel and/or an increase in myofibril number. However, some evidence suggests that myofibrillar protein content may be diluted through sarcoplasmic expansion as fCSA increases occur. Furthermore, and perhaps more problematic, numerous investigations have reported pre-to-post training change scores in various measures of hypertrophy are poorly associated The current review first provides a brief description of skeletal muscle composition and structure. We then provide a historical overview of muscle hypertrophy assessment. Next, current-day methods commonly used to assess skeletal muscle hypertrophy at the molecular, microscopic, and macroscopic levels in response to training are examined with attention directed to studies reporting ultrastructural and muscle protein concentrations. Finally, we critically evaluate the biological construct of skeletal muscle hypertrophy, propose potential operational definitions, and provide suggestions for consideration in hopes of guiding future research in this area.